Bias-Dependent Conduction-Induced Bimodal Weibull Distribution of the Time-Dependent Dielectric Breakdown in GaN MIS-HEMTs - Sun, Haozhe; Wen Lei; Jianguo Chen; Jin, Yufeng; Wang, Maojun (IEEE TRANSACTIONS ON ELECTRON DEVICES, 2022)
In this paper, we reported the mechanism of a bimodal Weibull distribution for TDDB of gate dielectric in GaN MISHEMT. It is shown that the properties of traps in the dielectric layer would have a great influence on the long time reliability and life time prediction process.